Existence of Arabicization Methods for Naturalising Contemporary Technical Vocabularies into the Arabic Language - Setiyadi, Alif Cahya; Anhar , Anhar; Anwar , Heru Saiful (REiLA : Journal of Research and Innovation in Language, 2022)
This research aims at studying Arabicization methods to provide counter knowledge for the overuse of transliterated terms and the abundance of Arabic equivalents for a technical term. It further promotes precise methods on how to Arabicize foreign words in the proper way. For this reason, this qualitative research focuses on studying Arabicization methods in traditional and modern Arabic traditions. The data are collected from several Arabic books, journals, and Arabic language academy reports. For the analysis, the inductive analysis approach is mainly employed to drive the general pattern of Arabicization’s methods through interpretation made from the previous discourse on Arabicization. The research concludes that the conventional vocabulary expanding techniques, including al-ishtiqāq, al-tarjamah, al-qiyās, al-naḥt, and al-majāz, are supposedly less effective and inefficient, while al-dakhīl brings only a few advantages but situating the Arabic language contaminated with numerous peculiar terms. Hence, the four methods of Arabicisation, which involve phonetical naturalisation, morphological naturalisation, filtering, and hybrid Arabicization, are fully considered precise methods. These methods play a crucial role in generating new Arabic technical-technological vocabularies that are mainly a product of the West with all its steps. Arabicisation provides more steps of naturalisation properties that arguably can be the best way to accommodate neologism.